Enhanced DES Algorithm Using Efficient Classical Algorithm - Abdulmunem, Inas Ali; Hoobi, Mays M. (Iraqi Journal of Science, 2024)
The privacy, confidentiality, and integrity of user information are very important concerns; therefore, cryptography is the solution to keep and satisfy these objectives. Encryption is the most important policy that is used to make transmitted messages have a high level of security and be so difficult to crack by attackers. The main aim of this research is divided into two parts: The aim of Part 1 is to obtain the highest level of complexity against the attacker by applying six classical cryptography algorithms to the same plain-text message. These six algorithms are Vigenère, Porta, Autokey, Beaufort, Trithemuis, and Gronsfeld. Also, in this part, several analysis tools are used to evaluate the performance of the six algorithms: entropy, histogram, and autocorrelation. Part 2 of this research aims to apply the results of Part 1 by using the best algorithm among these six algorithms (Vigenère) to improve the security level of the Data Encryption Standard (DES) algorithm by applying two experiments for two hybrid ciphering models. Each experiment has three cases. The first experiment included three cases: the first case included ciphering plain text by using only the Vigenère algorithm, the second case included ciphering plain text by using only the ECB DES algorithm, and the third case included multilevel ciphering plain text by using Vigenère and then ECB DES algorithms, while the second experiment for the second hybrid ciphering model included the same cases as the first experiment but applied CBC DES, another type of DES algorithm. The results of this research indicated different efficiency levels of six classical algorithms, and the Vigenère algorithm is the best and offers the highest level of complexity among the used algorithms. In addition, the Vigenère algorithm can be used to enhance the security level of cryptography algorithms and increase the complexity of cracking ciphertext when combined with another algorithm like the DES algorithm.